Pembelajaran Bermakna sebagai Manifestasi Tafaqquh fid-Din dalam Pendidikan Islam di Era Informasi - Rizki, Zaki Yazidatur; Aripin, Syamsul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Pembelajaran bermakna is an important foundation in Islamic Religious Education (IRE) to achieve the goal of tafaqquh fid-din in the information age. This study uses a literature review method with a qualitative approach to analyze the conceptual relationship between David Ausubel's pembelajaran bermakna theory and the principles of tafaqquh fid-din in the context of digital challenges. The findings show that pembelajaran bermakna can be viewed as a pedagogical manifestation of tafaqquh fid-din, which emphasizes a comprehensive, reflective, and applicable process of deepening religious understanding. The information age presents serious challenges in the form of misinformation, extreme content, and low digital literacy, but it also opens opportunities through the integration of meaningful technology. Implementation strategies include inquiry learning based on Islamic values, the use of measured digital media, deep reflection and contemplation, and the integration of general and religious knowledge. This study recommends a fundamental transformation in the design of Islamic education by adopting a holistic-integrative model, changing the role of teachers as murabbi (pembimbing spiritual) and information curators, and a comprehensive evaluation system covering cognitive, affective, and psychomotor aspects. The theoretical and practical implications show that modern Islamic education requires an integrative approach that combines the strengths of theory with pembelajaran bermakna practices to produce students who are faithful, have noble character, think critically, and are ready to contribute in the digital age.